2001
DOI: 10.1002/polb.10084
|View full text |Cite
|
Sign up to set email alerts
|

Persistent spectral hole‐burning study on dendrimer porphyrins

Abstract: We report the first results of persistent spectral hole burning of dendrimer porphyrins having three‐, four‐, or five‐layered aryl ether dendritic arrays. We evaluate structural relaxations of dendrimer framework around the porphyrin core at low temperatures. A large environmental change around the porphyrin core, as evaluated from the hole area, was suppressed in dendrimer porphyrins of higher generation numbers, whereas a small environmental change, as evaluated from hole width, showed no dependence on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…12b The effective distance within which the porphyrin molecule can sense the structural relaxation of surrounding polymer chains was also ascertained to be 2.5 nm by PHB of dendrimers with a TPP core. 17 We confirmed that PHB is very useful for studying the nanoenvironments around the chromophores. The nanoscopic aggregation in bulk films of the amphiphilic random copolymers already reported by TEM 11 has been recently confirmed by PHB temperature cycle experiments.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…12b The effective distance within which the porphyrin molecule can sense the structural relaxation of surrounding polymer chains was also ascertained to be 2.5 nm by PHB of dendrimers with a TPP core. 17 We confirmed that PHB is very useful for studying the nanoenvironments around the chromophores. The nanoscopic aggregation in bulk films of the amphiphilic random copolymers already reported by TEM 11 has been recently confirmed by PHB temperature cycle experiments.…”
Section: Introductionsupporting
confidence: 70%
“…The hole widths of the unimers in PVA were independent of the unimers radii, which suggested the structural relaxation detected by PHB temperature cycle experiments was effective within 2.3 nm 12b. The effective distance within which the porphyrin molecule can sense the structural relaxation of surrounding polymer chains was also ascertained to be 2.5 nm by PHB of dendrimers with a TPP core . We confirmed that PHB is very useful for studying the nanoenvironments around the chromophores.…”
Section: Introductionsupporting
confidence: 58%
“…The studies have dealt with for example light harvesting, 21,26,27 energy transfer, 8,28-31 and site isolation. 3,15,[32][33][34][35][36] A large number of different dendrimers 26,[28][29][30][37][38][39] have been utilized, ranging from Fre ´chet-type benzyl ether dendrimers 35,[40][41][42][43] to glutamic dendrimers. 15,36,44 Very little work has been conducted with the bis-MPA (2,2-bis(methylol)propionic acid) repeating unit.…”
Section: Introductionmentioning
confidence: 99%